(untitled) (Research, Society and Development, 2020)
The aim of the study was to develop technology for generating panels with MDF residues and gelatinized, chemically and physically modified corn starch. In the research, corn starch and sawdust MDF processing residues were used for panel formation and comparison with characteristics of commercial MDF. To support the study, the Brazilian standard ABNT NBR 15316-1 was used as a standard. As for the methodologies, treatments with lactic acid, acetic anhydride and by annealing technique were applied to change the properties of corn starch for later formation of the adhesive. The panels were formed in the cold and hot pressing process and physical tests were carried out to compare with the conventional MDF board and chemical tests to check the starch modification. The chemically modified starches underwent changes in their structure, compared to the starch in natura. The plate formed by sawdust and unmodified corn starch showed better parameters in comparison with the plates formed with sawdust and modified corn starch resisting the perpendicular traction of 5.95 kg / cm². It was observed that, although the boards produced by fresh corn starch have a lower resistance capacity than the usual MDF boards, they are alternatives to use part of the residue generated for a more noble application and that the adhesive has proved effective in forming the panels and eliminate possible substances undesirable to the environment.